Excessive Daytime Sleepiness in a Real-World Study of Participants With OSA With or Without Comorbid Depression. (April 2023) - Parthasarathy, Sairam; Zhang, Jerry; Hyman, Danielle; Doherty, James; Saad, Ragy; Fox, Benjamin; Marshall, Nell J.; Parks, Gregory
Abstract: Background: Obstructive sleep apnea (OSA) is a sleep disorder that is highly comorbid with psychiatric disorders, including depression and anxiety. Excessive daytime sleepiness (EDS) is common in psychiatric disorders and OSA. In participants with OSA, EDS can persist despite use of positive airway pressure (PAP) therapy. This analysis of real-world data aimed to describe EDS and its relationship with PAP use in participants with and without depression. Methods: US residents (≥18 years of age, self-reported physician diagnosis of OSA [from 1/1/2015 to 3/31/2020]) completed a survey in Evidation Health's Achievement app assessing subjective levels of sleepiness (Epworth Sleepiness Scale [ESS]) and self-reported PAP usage, categorized as nonuse (no PAP use), nonadherent (<4 h/night or <5 d/wk), intermediate (4-6 h/night, ≥5 d/wk), or highly adherent (≥6 h/night, ≥5 d/wk). ESS score >10 defined EDS. A linear model assessed relationships between PAP use and ESS score. P- values are uncontrolled for multiplicity (nominal). Results: In total, 2289 participants (EDS, n=972; no EDS, n=1317) completed the survey (50.3% female; 82.5% White; mean±standard deviation [SD] age, 44.8 ± 11.1 years). Anxiety and depression were the most common comorbidities and were more common in participants with EDS (49% and 49%, respectively) than those without EDS (41% and 37%, respectively). Overall, EDS was more common among participants with comorbid depression (49%) than those without (38%), even among highly adherent PAP users (46% vs 30%, respectively). In a linear model (PAP users only), an additional 1 h/night of PAP use was associated with lower ESS scores in the subgroup of participants without depression (n=928; estimate [SE], −0.42 [0.09]; P <0.05), but not in the subgroup with depression (n=661; estimate [SE], −0.15 [0.10]; P >0.05). In a sensitivity analysis that excluded participants using medications that cause sleepiness, PAP use was associated with lower ESS scores regardless of depression status; however, EDS remained more common in participants with comorbid depression (46%) than in those without (36%). Conclusions: In this real-world population of participants with OSA, those with EDS were more likely to have comorbid anxiety or depression. EDS was more common in participants with comorbid depression than those without, even with highly adherent PAP use. PAP use was associated with lower ESS scores in participants without comorbid depression, but not in those with comorbid depression; the use of medications that cause sleepiness may contribute to but does not fully explain this phenomenon. Funding: Axsome Therapeutics and Jazz Pharmaceuticals